ANALIS HUKUM TERHADAP TERJADINYA PEMBATALAN PERKAWINAN KARENA PEMALSUAN IDENTITAS - Catur Widia Astuti Puspita Sari (Kajian Hukum, 2021)
The importance of the meaning and purpose of marriage, then everything related to marriage must be regulated by law in detail and complete. A marriage is said to be valid if all the conditions and its pillars are fulfilled or carried out perfectly and do not violate the prohibition of marriage. The cancellation of a marriage is determined after a decision from the Religious Courts which has permanent legal authority and does not apply to participate since the time of the marriage. To obtain a decision from the court on the annulment of a marriage, a person is required to proceed before the court in the jurisdiction where the marriage was held or where the two husbands and wives live. Based on the decision of the case No.2447/Pdt.G/2015/PA.Mdn which occurred at the Medan Religious Court, because the groom claimed to be a dead widower, while the truth was that he still had a legal wife residing in Medan. Because of his dishonesty to the marriage registrar regarding his status. This research is a normative or doctrinal legal research. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The paper concludes that the reasons for the annulment of marriage in Decision No. 2447/2015/Pdt.G.Mdn carried out by the judge in his consideration was in accordance with the regulations in the Marriage Law and the Compilation of Islamic Law (KHI)